PENGARUH STAKEHOLDER ENGAGEMENT, SOCIAL MAPPING DAN PENERAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KETERCAPAIAN SOCIAL LICENSE TO OPERATE) - Hendra, Hendra; Rachmawati, Ike Kusdyah (Jurnal Ilmiah Global Education, 2023)
This study intends to analyze the effect of stakeholder engagement, social mapping and the implementation of Corporate social responsibility on the achievement of a social license to operate at PT Semen Gresik Rembang Factory. This study used a sampling technique by taking purposive sampling as a sample. The instrument for taking the questionnaire was for 355 respondents, namely the people who are in the environment of PT Semen Gresik Rembang Factory. The research data was processed as a quantitative description using path analysis techniques using application software and supported by primary data using a questionnaire. The results of this study indicate that: (1) Stakeholder engagement has a significant effect on the achievement of a social license to operate; (2) Social mapping has a significant effect on achieving a social license to operate; (3) corporate social responsibility has a significant effect on the achievement of a social license to operate; (4) Stakeholder engagement, social mapping and corporate social responsibility simultaneously influence the achievement of a social license to operate.